The Role of Duration, Digital Characters as Visual Stimulation in Non-English Animation Trailer - Ahmad Azaini, Bin Abdul Manaf; Mohd Rosli, Bin Arshad; Jong, Sze Joon; Wan Jamarul Imran, Bin Wan Abdullah Thani; Ruslan, Bin Rahim (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The research investigates the observation on youth by viewing foreign language trailers, the outcome testing can have a distinct effect on the stimulation of the audiences. The experiment conducted to investigate the correlation analysis which, based on visuals, genre, animation style, character designs, audio (soundtracks) and voices used in non-mainstream foreign language animation trailers. In this study, the test comprised of 60 youth from peninsular Malaysia and Sarawak to categorize factors of characters, violence content, genre, unfamiliar voices and audio sample from the respective foreign animation trailers. Interestingly, the finding suggested highest relationship on main characters, antagonist should appear in trailers (.853) without help of foreign voices, and of course the shortest duration plays towards intention to watch the full film, therefore the results on longest trailer duration were not stimulating. The significant of the research on trailers is imperative to determine the factors among Malaysian youth in cinema, for the development and digital creation of domestic animation film. The outcome is valuable for digital content directors, NLE(Non-Linear Editing) operators and creative marketers to promote content prior to cinemas release.